Pengembangan Sistem Informasi Integrasi Data Dapodik dengan Data Kependudukan berbasis Web di Dinas Pendidikan dan Kebudayaan Kota Pasuruan - R Bagus Bagaskara; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
He Office of Education and Culture of the City of Pasuruan City is an element of the implementation of the Pasuruan City Regional Government in providing services in the field of Education and Culture of the City of Pasuruan which are required to improve services. So far, manual reporting is time-consuming and labor- intensive. Based on these problems, it is necessary to integrate information system data with web-based population data, as well as the development of this system using the waterfall model method where the system is tested using the Validation Testing method. , design, implementation and testing of systems. The test results on this system indicate that the system is running as expected and is able to facilitate data reporting at the Pasuruan City Education and Culture Office